Resistance of Black Bengal goat to Haemonchus contortus - Retee, NN; Mondal, MMH; Omar, AI; Periasamy, K; Garcia, JF; Notter, DR; Faruque, MO (Progressive Agriculture, 2019)
Artificial challenge trial and field trial were carried out in two populations of Black Bengal goat in Bangladesh to evaluate the resistance to Haemonchus Contortus-a major gastrointestinal nematode in goat. Artificial challenge trial revealed that there was no difference in susceptibility of H. contortus in Black Bengal goat of hilly region (BBH) and Black Bengal goat of western region (BBW). In absence of parasitic infection, growth rate of kids of both populations were almost equal. Field trial was conducted with kids of BBW population to find out the within breed variation. Numerically, there was variation among the individuals for parasitic load however the results were statistically insignificant (p > 0.05). At individual level, the parasite load ranged from 100 to 400 eggs per gram (epg). The location of villages, age and sex of kids did not influence on the parasitic load of kids. There was no interaction for location, age and sex for body weight at day 8. The Packed Cell Volume and Hemoglobin values differed significantly (p < 0.01) due to age of kids at day 8 and 28 after deworming. The results indicate that Black Bengal goat can be considered as resilience to H. contortus. Progressive Agriculture 30 (1): 55-64, 2019